Unmet care needs of older people: A scoping review - Kalánková, Dominika; Stolt, Minna; Scott, Philomena Anne; Papastavrou, Evridiki; Suhonen, Riitta A. (My University, 2021)
The aim was to synthesize the findings of empirical research about the unmet nursing care needs of older people, mainly from their point of view, from all settings, focusing on (1) methodological approaches, (2) relevant concepts and terminology and (3) type, nature and ethical issues raised in the investigations. A scoping review after Arksey and O’Malley. Two electronic databases, MEDLINE/PubMed and CINAHL (from earliest to December 2019) were used. Systematic search protocol was developed using several terms for unmet care needs and missed care. Using a three-step retrieval process, peer-reviewed, empirical studies concerning the unmet care needs of older people in care settings, published in English were included. An inductive content analysis was used to analyse the results of the included studies (n = 53). The most frequently used investigation method was the questionnaire survey seeking the opinions of older people, informal caregivers or healthcare professionals. The unmet care needs identified using the World Health Organization classification were categorized as physical, psychosocial and spiritual, and mostly described individuals’ experiences, though some discussed unmet care needs at an organizational level. The ethical issues raised related to the clinical prioritization of tasks associated with failing to carry out nursing care activities needed. The unmet care needs highlighted in this review are related to poor patient outcomes. The needs of institutionalized older patients remain under-diagnosed and thus, untreated. Negative care outcomes generate a range of serious practical issues for older people in care institutions, which, in turn, raises ethical issues that need to be addressed. Unmet care needs may lead to marginalization, discrimination and inequality in care and service delivery. Further studies are required about patients’ expectations when they are admitted to hospital settings, or training of nurses in terms of understanding the complex needs of older persons.
Keywords: Missed care; Nursing; Older people; Rationing; Scoping review; Unfinished care; Unmet care needs